(untitled) (Applied Biological Research, 2012)
An experiment was conducted at Central Institute of Temperate Horticulture, Srinagar, Kashmir on almond (Prunus dulcis Mill.) cv. ‘Shalimar’ plantation to standardize the water requirement for yield optimization in almond. The study revealed that vegetatively propagated almond plants positively responded to irrigation. The irrigation, applied according to different ETc levels, improved yield and yield contributing attributes of almond significantly. Highest nut yield (2.42 kg tree-1) was recorded at 100% ETc during 1st year of experimentation which increased to 2.91 kg tree-1in the subsequent year. Similarly, highest shelling percentage (53%) was recorded in nuts receiving full irrigation during the 2nd year of experimentation. The highest yield and yield contributing attributes of almond, recorded at 100% ETc level of irrigation, were statistically at par with measured parameters recorded at 75% ETc level of irrigation.